Relationship between adolescents’ self-efficacy for protection from substance abuse and parental attachment levels - Ayhan, Fatma; Genç, Mehtap; Türkmen, Ayşe Sonay (Journal of Dependence, 2021)
Objective: This study was conducted to determine the correlation between self-efficacy for substance addiction prevention and parental attachment levels of adolescents. Method: A total of 120 adolescents participated in this study, which was conducted as a descriptive correlational study. The data collection tools include "Personal Information Form", "Self-Efficacy Scale for Protection from Substance Addiction (SESPSA)" and "Parental Bonding Instrument (PBI)" applied to the participants. Results: Adolescents’ average SESPSA total score is 76.47 ± 28.31. A significant correlation was found between the average total and subscale SESPSA scores and certain demographic characteristics of adolescents. It was revealed that the protection levels of female adolescents, whose mothers were secondary school graduates had higher protection from substance addiction. It was discovered that there was a significant difference between adolescents’ substance using status and parental attachment rates. Conclusion: Therefore, adolescents are at risk for substance abuse. Especially as the low maternal education level, male gender and negative parental attitudes increase this risk ratio for adolescents. It is recommended to plan protection, prevention and early diagnosis and for these groups, which are found to have a higher risk for substance addiction.